Genetic Manifestations and Phenotype Spectrum in Infants With Feeding Difficulty - Mingyu Han; Wei Shi; Xiangxiang Chen; Dingwen Wu; Yi Sun; Weiyan Wang; Canyang Zhan; Lingling Hu; Tianming Yuan (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Feeding difficulties frequently co‐occur with multisystem disorders attributed to rare genetic diseases. In this study, we aimed to describe the genetic manifestations and phenotype spectrum in infants experiencing feeding difficulties. Methods This case series included infants under 6 months old with feeding difficulties admitted to the neonatal department of Children's Hospital, Zhejiang University School of Medicine from October 2018 to May 2022. All infants underwent whole‐exome sequencing (WES) during hospitalisation, and their clinical phenotypes and genetic results were analyzed. Results Among 28 infants studied, nine were preterm and 19 were full‐term. Median admission age was 13.5 days (IQR 6.5, 35), with a median hospital stay of 16 days (IQR 10.5, 30). Overall, 12 (42.9%) cases were complicated with multiple malformations. Abnormal muscle tone (53.6%) and neurological issues (42.9%) were notable prevalent in these infants. Cranial MR abnormalities were noted in 96.2% of cases. Based on the combined analysis of WES results and clinical phenotypes, a total of 22 (78.3%) patients displayed disease‐related genetic variation identified through WES; among them, 15 (53.6%) patients received genetic diagnoses, while 7 (25%) patients were suspected diagnoses. Positive findings were more frequent in full‐term (89.5%) than preterm infants (55.6%). Ultimately, 24 (85.7%) patients were discharged alive, with 75% requiring post‐discharge tube feeding. Following discharge, five patients developed new symptoms linked to genetic variants, and two patients died. Conclusions Feeding difficulty may constitute a facet of the phenotypic spectrum of rare genetic diseases. Whole‐exome sequencing can enhance molecular diagnosis accuracy for infants with feeding difficulties.